Radiological and Clinical Prognostic Factors of Recurrence of Subacute and Chronic Subdural Hematomas - Paliulytė, Milda; Šustickas Gytis (Lietuvos chirurgija, 2023)
Objectives. To assess characteristic data of patients hospitalized due to subacute subdural hematomas (SSDHs) and chronic subdural hematomas (CSDHs) and to evaluate radiological findings and establish predictors of hematoma recurrence of SSDHs and CSDHs patient populations. Methods. 149 patients with SSDHs and CSDHs who underwent surgery at Kaunas Clinics Neurosurgery Department from 2020 to 2021 were analyzed. Based on recurrence rate, patients were divided into different subtypes based on computer tomography (CT) imaging. Descriptive analysis, hypothesis testing and correlation matrix were performed using Excel spreadsheet and R programming language with the significance at p-value < 0.05. Results. Out of 149 patients, SSDHs and CSDHs were observed in 89 males (59.6%) and 60 (40.3%) females. Mean of the patients age was 71.1±15 years. Dichotomizing results based on recurrence (cut-off value of 25%), 2 groups were made: 1) low reoperation rate –hypodense sedimented (10%), isodense (21.6%), hypodense (22.2%); 2) high reoperation rate – hypodense bridging (26.7%), hypodense trabecular (27.8%), hypodense with acute bleeding (28.6%), hypodense laminar (30%), isodense with acute bleeding (33.3%). Conclusion. It is concluded that based on 25% reoperation rate high-recurrence and low-recurrence chronic subdural hematomas groups were similar in all terms apart from the hematoma thickness (mm), which leads to a fact that radiological appearance of higher recurrence hematomas should be carefully taken into consideration.